К вопросу энергосбережения при выпаривании растворов - Нечипоренко, Дмитрий Игоревич; Фокин, Виталий Сергеевич; Пономаренко, Евгения Дмитриевна; Нечипоренко, С. Д. (НТУ "ХПИ", 2005)
In paper the problems of evaporation in multibody evaporating installations surveyed. The analysis of experiment is carried out at a modification of an amount solution at collateral a feeding. The influence of feeding on expenditure of heating steam and area of surface of heat exchange is investigated.
Keywords: энергозатраты; вредные выбросы; тепловые схемы; выпарная установка; термонестойкие растворы; греющая камера; математическое моделирование